Neutrophil Inflammatory Response Is Downregulated by Uptake of Superparamagnetic Iron Oxide Nanoparticle Therapeutics - Garcia, Gustavo; Kim, Min-Ho; Morikis, Vasilios Aris; Simon, Scott I. (Frontiers in Immunology, 2020)
Superparamagnetic iron oxide nanoparticles (SPION) are employed as diagnostics and therapeutics following intravenous delivery for the treatment of iron deficiency anemia (IDA) in adult patients with chronic kidney failure. Neutrophils are the first defense against blood borne foreign insult and recruit to vascular sites of inflammation via a sequential process that is characterized by adhesive capture, rolling, and shear resistant arrest. A primary chemotactic agonist presented on the glycocalyx of inflamed endothelium is IL-8, which upon binding to membrane CXCR activates a suite of responses in neutrophils. An early response is degranulation with accompanying upregulation of β2-integrin (CD11/CD18) and shedding of L-selectin (CD62L) receptors, which exert differential effects on the efficiency of endothelial recruitment. Feraheme is an FDA approved SPION treatment for IDA, but its effect on the innate immune response of neutrophils during inflammation has not been reported. Here, we studied the immunomodulatory effects of Feraheme on neutrophils freshly isolated from healthy human subjects and stimulated in suspension or on inflammatory substrates with IL-8. Cells treated with Feraheme exhibited reduced sensitivity to stimulation with IL-8, indicated by reduced upregulation of membrane CD11b/CD18 receptors, high affinity (HA) CD18, and shedding of CD62L. Feraheme also inhibited N-formyl-Met-Leu-Phe (fMLP) induced reactive oxygen species production. Neutrophil rolling, arrest, and migration was assessed in vascular mimetic microfluidic channels coated with E-selectin and ICAM-1 to simulate inflamed endothelium. Neutrophils exposed to Feraheme rolled faster on E-selectin and arrested less frequently on ICAM-1, in a manner dependent upon SPION concentration. Subsequent neutrophil shape change, and migration were also significantly inhibited in the presence of Feraheme. Lastly, Feraheme accelerated clearance of cytosolic calcium after IL-8 induced flux. We conclude that the presence of Feraheme and uptake by neutrophils in circulation may inhibit chemotactic activation and downregulate their normal recruitment under shear flow at vascular sites of inflammation by accelerating calcium sequestration.